Etnopedagogi Batang Garing Suku Dayak Ngaju sebagai Nilai Pendidikan Karakter Peduli Lingkungan - Wurdianto, Kukuh; Norsandi, Dedy; Fitriana, Evi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to analyze the Batang Garing symbol of the Dayak Ngaju tribe in Central Kalimantan based on an ethnopedagogical perspective, especially in environmental care character education. The research design used is an ethnographic research design that focuses on the Batang Garing symbol. This ethnographic research consists of 6 stages, selecting an ethnographic project; asking ethnographic questions; collecting ethnographic data; taking notes; analyzing the data, and writing the results of the ethnographic research. The results of this study explain that Ethno pedagogy raises the values of local wisdom as an important part of the educational process and the civilizing process. Dayak Ngaju tribe adheres to a conservationist understanding which is taken from the philosophy of the Batang Garing symbol which contributes to treating the natural environment. the value of character education in each part of the Batang Garing symbol, among others: the "Enggang" symbol contains a religious character; the bunu symbol contains the character of responsibility; the support symbol contains the character of caring for the environment; the garanuhing symbol contains a peace-loving character; the dawen dandang tingang symbol contains the value of caring for the environment; the Balanga symbol contains the value of tolerance; and the symbol of Batu Nindan Tarung Island contains the values of caring for the environment, responsibility and religion. The internalization of the environmental care character in the Batang Garing symbol is not separated from other parts of the symbol because in the internalization of the character all components are interrelated.